Exploring the Impacts of Food Technology Beliefs, Evaluations, and Media Consumption on Attitudes Toward Nanofood in Singapore - Kong, Wei Yi (2018)
This paper aims to explore factors influencing people’s attitudes toward nanofood in Singapore. Drawing on expectancy-value theories, this paper conducted a web-based survey (N=1,001) to measure the influences of beliefs of food technology, evaluations of food naturalness, and media consumption about food safety on attitudes toward nanofood and willingness to purchase nanofood products. Results suggested that attitudes toward nanofood are directly shaped by beliefs of food technology, whose influence is partially mediated by media consumption. Attitudes toward nanofood were also positively related to willingness to purchase nanofood. However, our study found no significant effect of food naturalness evaluations on attitudes toward nanofood. This paper helps to elucidate the significance of favorable perceptions of food technology and informative media messages in encouraging positive attitudes toward nanofood.